2014
DOI: 10.1136/archdischild-2014-306576.39
|View full text |Cite
|
Sign up to set email alerts
|

8.10 Cranial ultrasound findings suggest that the injury pathway may begin many hours before delivery in encephalopathic infants in Uganda

Abstract: In sub-Saharan Africa, the timing and nature of brain injury and their relation to mortality in neonatal encephalopathy (NE) is unknown. Aim To evaluate cranial ultrasound (cUS) scans from term Ugandan infants with NE and unaffected controls for evidence of established/evolving brain injury. Methods Infants were recruited to a case-control study at Mulago Hospital, Kampala. Cases had NE (score1 >5). Controls were randomly selected unaffected term infants. All had cUS scans <36 h; surviving cases had day 4/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The babies will have a cranial ultrasound scan on admission, at 24 h and 3–4 days for detection of malformations, bleeds, loss of normal tissue differentiation and evolving tissue injury. 26 Amplitude-integrated EEG (aEEG) will be performed over the first 48 h, as part of standard clinical care. The aEEG background activity will be classified according to voltage criteria and by background pattern.…”
Section: Methods and Designmentioning
confidence: 99%
“…The babies will have a cranial ultrasound scan on admission, at 24 h and 3–4 days for detection of malformations, bleeds, loss of normal tissue differentiation and evolving tissue injury. 26 Amplitude-integrated EEG (aEEG) will be performed over the first 48 h, as part of standard clinical care. The aEEG background activity will be classified according to voltage criteria and by background pattern.…”
Section: Methods and Designmentioning
confidence: 99%
“…Emerging evidence from LMIC suggests similar perinatal origins of brain injury. Tann et al [35] reported that 80% of the early cranial ultrasound (USG) scans were normal in encephalopathic babies admitted to a Sub-Saharan African neonatal unit, and none of them had evidence of established brain injury. Although the utility of USG in term encephalopathic infants is limited [36], these findings are similar to the cerebral MRI reported by Lally et al from a South Indian cohort (n = 54), in which none of the encephalopathic babies had evidence of established brain injury.…”
Section: Concerns About Established Brain Injurymentioning
confidence: 99%